Small-sized computed tomography system with rotating gantry - Jantanayingyong, V.; Chanwimalueang, T.; Srisuk, N.; Pintavirooj, C. (My University, 2010)
Small-sized computed tomography system with rotating gantry is presented in this paper. System calibration was performed before achieving the projection data. An object placed on platform was exposed by the x-ray every two degrees of rotating angle. Thus, 180 projection data were performed in this study. Finally, Feldkamp algorithm based on a 3D filtered backprojeciton was employed to reconstruct cross sectional images. The result shows that cross sectional images obtained from small-sized computed tomography were satisfactory. In conclusion, the small-sized computed tomography presented in this study is capable to construct the cross sectional images. Moreover, 3D model reconstructed from these cross sectional images will be performed in the future work.
Keywords: Backprojection; CT; Feldkamp; Image reconstruction